Synthesis and Reactivity of 3H-1,2-dithiole-3-thiones - Oleg A. Rakitin (Molecules, 2021)
3H-1,2-Dithiole-3-thiones are among the best studied classes of polysulfur-containing heterocycles due to the almost explosive recent interest in these compounds as sources of hydrogen sulfide as an endogenously produced gaseous signaling molecule. This review covers the recent developments in the synthesis of these heterocycles, including both well-known procedures and important novel transformations for building the 1,2-dithiole-3-thione ring. Diverse ring transformations of 3H-1,2-dithiole-3-thiones into various heterocyclic systems through 1,3-dipolar cycloaddition, replacement of one or two sulfur atoms to form carbon- and carbon-nitrogen containing moieties, and other unexpected reactions are considered.